1990
DOI: 10.1093/sleep/13.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness, Performance, Mood, Nocturnal Sleep: The Effect of Benzodiazepine and Caffeine on Their Relationship

Abstract: The present study was part of a larger 3-day, 2-night double-blind parallel group design in which 80 young adult men were divided into eight treatment groups to examine the effects of benzodiazepines and caffeine on nocturnal sleep and daytime sleepiness, performance, and mood. The present study was done to examine further the relationship among daytime sleepiness, performance, mood, and nocturnal sleep and to determine if and how these relationships were affected by the nighttime use of benzodiazepine and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 0 publications
4
22
1
1
Order By: Relevance
“…As reported previously [36,37], these results indicate a poor agreement between reported sleepiness and objective sleepiness as measured by the MSLT.…”
Section: Discussionsupporting
confidence: 78%
“…As reported previously [36,37], these results indicate a poor agreement between reported sleepiness and objective sleepiness as measured by the MSLT.…”
Section: Discussionsupporting
confidence: 78%
“…That is, caffeine consumption failed to benefit the performance of participants who were free of the negative effects of acute caffeine withdrawal, even in the context of low alertness induced by sleep restriction. This is a key result, because it contradicts suggestions that caffeine is especially beneficial for performance when alertness is low (e.g., Johnson et al 1990;Lorist et al 1994;Smith et al 1994;Horne and Reyner 1996;Lieberman et al 2002;Reyner and Horne 2002;Wesensten et al 2002). Caffeine did affect the cognitive performance of the ONW participants, but merely to prevent yet further deterioration in their poorer pre-treatment performance.…”
Section: Discussioncontrasting
confidence: 59%
“…Consequently, it remains possible that there are circumstances under which caffeine consumption will bring about a significant net improvement of functioning. In particular, it has been suggested that caffeine is most likely to benefit performance when alertness is low (e.g., Johnson et al 1990;Lorist et al 1994;Smith et al 1994;Horne and Reyner 1996;Lieberman et al 2002;Reyner and Horne 2002;Wesensten et al 2002). Accordingly, the present study investigated the effects of caffeine on self-rated mood and alertness, and performance of various cognitive and psychomotor tasks in LTW and ONW participants whose sleep had been restricted to 5 h on the night before testing.…”
Section: Introductionmentioning
confidence: 96%
“…Subjective sleepiness, as measured by the SSS, was greater in the control group but was not modified by the drug. The divergence between subjective and objective values is not surprising, since it has clearly been demonstrated that subjective sleepiness is usually not related to the subject's actual propensity to fall asleep (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%